O trabalho da mulher na agricultura familiar de Paraíso do Sul/RS: o caso da associação das trabalhadoras rurais - Machado, Denise Lenise (2021)
Culturally, constructed and disseminated, the role played by women has always been viewed in a subordinate way to that of the male figure. They are still the ones who occupy most of the positions considered to be superior and prestigious. The differences established between men and women are perceived in all spaces, reaffirming male privileges and the predominant hegemonic thinking. In the Brazilian rural environment, this uplifting of the male figure is still perceived in the most diverse media: from peasant agriculture to agribusiness. Women, often undervalued as workers, occupy the position of assistants in the work carried out in the family production unit, with the justification that their work does not generate economic value, since it is concentrated in the family, private sphere, not establishing itself as a productive value. In the search for the valorization of women, in a patriarchal society that has a lot to evolve, the present work sought together with the Association of Rural Workers of Paraíso do Sul/ RS to know and recognize the work performed by rural women and their meanings in the territory. It also sought to understand how groups are articulated and organized and their contribution to building the empowerment of rural workers. In this context, the research aims to answer the following question: how the work of family farmers, members of the Association of Rural Workers of Paraíso do Sul/ RS, has contributed to building the empowerment of these women, as well as strengthening the family farming in the territory? By studying the work of rural women, in family farming, and how it is characterized, it provided an understanding of how the relations existing within the production unit occur, referring to the division established between the sexes, which ends up reflecting on economic relations, social and cultural factors established in society. In addition, it brought results related to groups, the association, the territory, in short, other social spaces. To achieve the proposed objectives, the use of qualitative and quantitative approaches was selected. As for the method used, the compression of the theme was sought in the dialectical method, as it approximates the reality of the research subjects. The collection of data for the purpose of carrying out this work was carried out in three main stages: the first concern was to collect information through bibliographic research; The second stage was devoted to field work, to diagnose the objectives proposed in this research in the territory, where interviews were carried out with the farmers and observations about the activities developed by them. In the third and last stage, the results were analyzed and discussed for the final writing of the dissertation. It should be noted that the Association of Rural Workers of Paraíso do Sul is an entity representing rural workers in the municipality. Becoming an essential tool of resistance and recognition to the work performed by these women, giving them visibility and a voice. Because by articulating collectively, it allows women farmers to go far beyond the family sphere and discuss agendas that are of common interest to them, that enable autonomy and the understanding of their importance for the development of family farming.